(untitled) (Journal of International Studies, 2020)
Transboundary haze pollution is an almost annual occurrence in Southeast Asia. Haze originates from peat and forest fires mostly in Indonesia, with Malaysia and Singapore suffering the worst of its effects. Most of these fires are manmade, and linked to land clearing activities of local and foreign commercial oil palm plantations. The regional nature of haze has concentrated mitigation activities at the ASEAN level. However these initiatives continually fail to effectively mitigate haze. This article argues that haze mitigation has been problematic due to the ASEAN style of regional engagement, which prioritizes the maintenance of national sovereignty. States are compelled to act in their national interests, as opposed to the collective regional interests. The economic importance of the oil palm sector to the states involved, coupled with traditionally close relationships between key economic actors and political elites, meant that the maintenance of the status quo, where major plantation companies could continue to clear land using the cost-effective method of burning, was of crucial national interest. Therefore, the ASEAN style of regional engagement has enabled member states to shape ASEAN initiatives to preserve the interests of these political and economic elite, while the public continue to suffer the haze.